Synthesis, Characterization and Biological Evaluation of New Benzamidine Derivatives: Antibiotics for Periimplantitis Causing Pathogen - Ajay, Jain; Mohammad Auwal, Sa'ad; S., Ugrappa; Kavitha, Ramasamy; Dharshini, Jagadeesan; Wu, Yuan Seng *; Pattabhiraman, Lalitha; Manickam, Ravichandran; Noor S., N.F.M.; Fuloria, Shivkanya; Fuloria, Neeraj Kumar (Asian Journal of Chemistry, 2023)
Periimplantitis (PI) is complex polymicrobial disease, which destroys implant-supporting tissue. Although facts suggest several synthetic inhibitors of periimplantitis causing bacteria (PCB), but the undesirable side effects of them limits their application. Hence, current investigation was intended to carry out the synthesis, characterization, in vitro antimicrobial evaluation and cytotoxicity (cell viability) analysis of new benzamidine derivatives (NBDs) against periimplantitis causing bacteria. Present study involved synthesis of 2-(4-((4-substituted)carbamothioyl)phenoxy)-N-(4-substituted benzylidene)acetohydrazide (4a-c) by treatment of different aromatic aldehydes with 2-(4-carbamothioylphenoxy)acetohydrazide (3), that was obtained by hydrazination of ethyl 2-(4-carbamothioylphenoxy)acetate (2), the derivative of 4-hydroxybenzothioamide (1). The synthesized compounds (NBDs) were subjected to FTIR, 1H NMR, 13C NMR and mass spectrometric characterization. All NBDs were further investigated for their antimicrobial potential (MIC and MBC) against P. gingivalis the PCB, using micro-broth dilution method. The NBDs were also tested for their cytotoxicity (cell viability) against HEK 293 cells using MTT assay. The present study successfully synthesized and elucidated the structures of the synthesized NBDs. The NBDs when tested against P. gingivalis exhibited MIC ranging between 62.5-500 μg/mL, whereas NBDs 4a and 4b exhibited MBC of 125 and 62.5 μg/mL respectively. Also, all NBDs exhibited weak cytotoxicity (cell viability more than 80%) against HEK 293 at 7.81 μg/mL. The significant antimicrobial activity of NBDs and higher cell viability (safety) against P. gingivalis supports their potential application in periimplantitis treatment, however these NBDs must be further investigated for the additional in vivo and clinical studies.